AN ANALYSIS OF ENGLISH-INDONESIAN TRANSLATION SHIFT IN THE GARDEN OF THE PROPHET BY KAHLIL GIBRAN - Yovinus Yovinus; Regina Regina; Ikhsanudin Ikhsanudin (Universitas Tanjungpura, 2020)
AbstractThis study was conducted in order to find out the types and the most dominant types of translation shifts that are used to translate English Noun Phrases in the Garden of the Prophet by Kahlil Gibran into Sri Kusdyantinah’s work of Taman Sang Nabi. The methodology used here is the qualitative research method, where the qualitative method is used to describe the data. The subject of this research is Kahlil Gibran’s work entitled the Garden of the Prophet and its translation in Bahasa Indonesia Taman Sang Nabi by Sri Kusdyantinah. The technique of collecting data is by identifying noun phrases found in the Garden of the Prophet, then, matched with the translation results in target language Taman Sang Nabi. The next step is to classify the translation results in any translation shift classification. In this research, the researcher applied the theory of translation shift proposed by Catford in analyzing the translation of noun phrases found in the Garden of the Prophet by Kahlil Gibran as the source language and its translation Taman Sang Nabi by Sri Kusdyantinah as the target language. Therefore, the most dominant type of the translation shift used by Sri Kusdyantinah is the Unit Shift. Keywords: Noun Phrases, Source Language, Target Language, Translation Shift